Meningitis micótica. Estudios de laboratorio y aspectos clínicos. - Lara Ruíz, Katheryn Sofía (2024)
Fungal meningitis is still uncommon; however, it is important to be alert to any symptoms, especially when having a weakened immune system, because it presents as a chronic, severe clinical picture and can lead to death. This research was carried out by means of a bibliographic review, with the aim of gathering scientific information on mycotic meningitis in terms of its clinical and laboratory behavior. It was a descriptive, documentary, retrospective study where 53 scientific articles were reviewed and 15 were selected by inclusion and exclusion criteria. The information was searched in databases such as Scielo, Elsevier, LILACS, Medigraphic, Dialnet, and BVS. With the analysis and discussion of the different authors, the study was concluded, achieving the proposed objectives, where it was evidenced that meningeal cryptococcosis is the most frequent, although there are other fungi capable of producing infection in the Central Nervous System, such as Candida, Coccidioides, and Histoplasma. Among the laboratory tests most commonly used to diagnose the disease are conventional microbiological methods such as direct examination with India ink, Gram, Giemsa, KOH, mycological culture media, PAS, and Grocott staining and PCR. Meningeal irritation, mental status alterations, endocranial hypertension, hydrocephalus, cranial nerve palsies, and seizures stand out as the most frequent clinical manifestations associated with immunosuppression. Male sex and age between the second and fifth decade of life predominated, although it can also appear at the extremes of life.